Tendency in Indonesian Newspaper Editorials: Genre and APPRAISAL Studies - Daniarsa, Hanna Latifani; Kartika-Ningsih, Harni (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2023)
Editorial is an important part of newspapers since the opinions expressed can influence the reader's point of view. The two major Indonesian news media that publish editorials in their newspapers are Kompas and Tempo. This study explores the potential differences in editorial characters between Kompas and Tempo regarding the 2024 election issue. To achieve this goal, the organizational structure of editorial texts is examined and their attitudinal tendencies are investigated. The method used in this study is analytical discourse framework by Systemic Functional Linguistics (SFL) in particular genre (Iedema, et al., 1994) and APPRAISAL framework (Martin & White, 2005). Based on the findings of genre and APPRAISAL in the text, it is revealed that the editorials of Tempo tend to be explicit in showing their position against 2024 election issues. Tempo uses the genre of media exposition and built their attitudinal tendencies by using negative evaluations. Unlike Tempo, Kompas tends to be implicit in showing their position against the said issue. They adopted media discussion genre and their attitudinal tendency is built using positive evaluations. The results of this study reveal that in examining the character of a media, an analysis of editorial text genres needs to be carried out before investigating its attitudinal tendencies.Keywords: APPRAISAL, genre, discourse analysis, newspaper, editorial